Multiple independent variants at the TERT locus are associated with telomere length and risks of breast and ovarian cancer - Bojesen, Stig Egil; Chang-Claude, Jenny; Burwinkel, Barbara; Marmé, Frederik; Hein, Rebecca; Brenner, Hermann; Hamann, Ute; Rudolph, Anja; Nickels, Stefan; Schneeweiss, Andreas; Sohn, Christof; Müller, Heiko; et al. (Nature genetics, 2013)
Stig Bojesen, Georgia Chenevix-Trench, Alison Dunning and colleagues report common variants at the TERT-CLPTM1L locus associated with mean telomere length measured in whole blood. They also identify associations at this locus to breast or ovarian cancer susceptibility and report functional studies in breast and ovarian cancer tissue and cell lines.
Gesehen am 01.12.2020